Implementation and Evaluation of A Gynecology eConsult Service Within A Large Health System [A287]. (May 2022) - Buddemeyer, Katherine; Hernandez, Sean; Dharod, Ajay; Shalowitz, David
Abstract : INTRODUCTION: Electronic consultations (eConsults) between primary care providers (PCPs) and specialty clinicians offer specialists' input into patient care without in-person consultation. However, limited data exist on process outcomes associated with implementing systemwide eConsult services for gynecologic care. METHODS: We reviewed all gynecology eConsults at our institution from program start in February 2020 to September 2021. Analyzed variables included content, completion time, and provider satisfaction. The eConsult data were contextualized within systemwide data regarding in-person consultation processes. RESULTS: Implementation required identification of gynecologists willing to answer eConsults through the electronic medical record and development of consult template text to ensure adequate information was presented. Educational outreach was provided to PCP practices on workflow. A total of 71 gynecology eConsults were analyzed. Mean time from submission to completion was 0.73 days; 85% required less than 15 minutes of specialists' time. Most common eConsults involved cervical cancer screening (32%), abnormal uterine bleeding (14%), contraception (14%), imaging (13%), and menopause (10%). Systemwide, 85% of eConsults were perceived as appropriate by specialists; 93% of PCPs reported being satisfied or extremely satisfied. Of the PCPs, 30% reported they would have initiated in-person consultations if eConsults were unavailable; systemwide, time from referral to in-person consultation was 32.8 days. CONCLUSION: Implementation of a gynecology eConsult program is feasible, minimally burdensome to specialists, and associated with high satisfaction among PCPs. In our system, successful eConsults improved timeliness of access to gynecologists' recommendations by several weeks. Future work is in progress to determine whether and how expansion of eConsult utilization can further improve access to gynecologic care.